2006
DOI: 10.1111/j.1365-2435.2006.01171.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal immunoglobulin concentration in Collared Flycatcher (Ficedula albicollis) eggs in relation to parental quality and laying order

Abstract: Summary 1.The immune system of newly hatched birds is relatively immature; therefore pathogens can be particularly virulent. Females transfer passive immunity in terms of immunoglobulins to the eggs to protect their young against infections in the crucial early life stages. 2. As transmission of antibodies is likely to be nutritionally costly, mothers are expected to allocate these components differentially to eggs according to their own condition, the quality of their mate or the laying order of eggs. 3. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 97 publications
2
50
0
Order By: Relevance
“…AICc ranking, delta values, likelihoods and weights and model r 2 for models of life-history effects on yolk IgY deposition. Analysis was done assuming a star phylogeny (OLS) and assuming stabilizing selection with drift (OU) using a tree compiled from the literature and presented in Cohen et al (2008 Grindstaff et al 2005) and comparable to estimates reported in Ficedula albicollis (0.63 mg ml 21 relative to chicken standard, Hargitai et al 2006). Several factors could contribute to the low levels measured in wild altricial birds.…”
Section: Discussionmentioning
confidence: 99%
“…AICc ranking, delta values, likelihoods and weights and model r 2 for models of life-history effects on yolk IgY deposition. Analysis was done assuming a star phylogeny (OLS) and assuming stabilizing selection with drift (OU) using a tree compiled from the literature and presented in Cohen et al (2008 Grindstaff et al 2005) and comparable to estimates reported in Ficedula albicollis (0.63 mg ml 21 relative to chicken standard, Hargitai et al 2006). Several factors could contribute to the low levels measured in wild altricial birds.…”
Section: Discussionmentioning
confidence: 99%
“…Breeding can result in stressful social dynamics that impact females differently. Stress can elevate or depress immunoglobulin production depending on its severity (Hargitai et al, 2006;Morales et al, 2004). Pied flycatchers with increased stress levels, as measured by heat-shock protein levels, laid eggs with higher concentrations of IgY (Morales et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Black-headed gulls provide the first laid egg with the most IgY (Groothuis et al, 2006), while collared flycatchers allocate the most IgY to the last egg in the clutch (Hargitai et al, 2006). Both species are asynchronously hatching species and earlier laid eggs usually have a higher chance of survival (Groothuis et al, 2006;Hargitai et al, 2006). Providing the first laid eggs with higher concentrations of IgY furthers their advantage, while distributing more IgY to later laid eggs may be an attempt to help them survive (Groothuis et al, 2006;Hargitai et al, 2006).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations